PROBLEMATIKA PROSES PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA SISWA TUNAWICARA DI SEKOLAH DASAR INKLUSI - Husnul Khotimah (Institut Agama Islam Negeri Kediri, 2019)
Abstract: This study aims to determine the problems that arise in the learning process of Islamic Education for speech impaired children at the Inclusion School. The school that is identic with education for all, has different characteristic students, both physical and mental. This research is a qualitative descriptive study with a case study approach. The research subject were speech impaired student, class teacher, religious teacher, special assistant teacher, and parents of student. The result of this study is there are many problems that arises in the proccess of Islamic Education learning for speech impaired children at the Inclusion school, includes (1) the difficulty of modifying existing curriculum for normal student dan student with special needs; (2) the lack of educators who have spaecial competencies such as religious teacher who are able to master sign language; (3) lack of school facilities and infrastucture that support learning proccess, especially for people with disabilities, likes a therapy device or phisycal aids for limbs that have deficiencies; (4) lack of ability to cooperate with other educational services, both normal and nonformal education service and (5) lack of time allocation given in understanding material due to differences in student’s abilities. The school has sought solution to minimize the problems, such as: (1) recruiting a number of competent educators; (2) collaborating with other parties such as providing an internship for psycology students from one of the state universities in Kediri; (3) holding activities outside the school that are useful for training the mental endurance of childrenwith special needs being more confident in other environment. Abstrak: Penelitian ini bertujuan untuk mengetahui problematika yang muncul dalam proses pembelajaran Pendidikan Agama Islam bagi Anak Tunawicara di Sekolah Inklusi. Hal ini diawali dengan pemaparan pelaksanaan proses pembelajaran dan menemukan problematika, serta diakhiri dengan solusi yang sudah dilakukan pihak sekolah dan solusi yang ditawarkan oleh peneliti. Penelitian ini merupakan penelitian deskriptif kualitatif dengan pendekatan studi kasus. Subyek penelitian adalah siswa tunawicara, guru kelas, guru agama, guru pendamping khusus, dan orang tua siswa. Metode penelitian menggunakan deskriptif kualitatif. Hasil penelitian ini adalah problematika yang muncul adalah Kurangnya tenaga pendidik yang memiliki keahlian khusus dalam menangani siswa tunawicara, kurangnya sarana dan prasarana yang mendukung pembelajaran, khususnya bagi penderita tunawicara, kurangnya alokasi waktu yang diberikan untuk memberikan pembelajaran bagi siswa tunawicara, dan kurangnya dukungan dari orang tua siswa. Sedangkan solusi yang sudah dilakukan oleh pihak sekolah untuk meminimalisir problematika diatas adalah: Menambah tenaga pendidik yang memiliki kompetensi di bidang Pendidikan Luar Biasa, mengajukan proposal kepada pihak yang berkepentingan agar memberikan bantuan dana untuk memenuhi sarana prasarana yang mendukung proses belajar mengajar, mengkaji ulang kurikulum yang telah berjalan saat ini dan menjalin kerjasama yang intens dengan wali murid.